(untitled) (MAUSAM, 1986)
Various models to study the effects of weather variables on rice yield at different stages of crop growth and to forecast its yield for Puri district have been attempted. The results indicated that above average maximum daily temperature had beneficial effects during ripening stage; detrimental effects during reproductive stage of the crop while in the initial growth, active and lag vegetative phase effects were fluctuating. The effect of increase in minimum temperature, was beneficial during initial, lag vegetative and reproductive stages, detrimental during ripening stage and fluctuating during active vegetative stage. Above average relative humidity and rainfall had beneficial effects throughout the growth and detrimental effects during ripening phase of the crop in general. The effects of rainfall and increase in number of rainy days were fluctuating up to lag vegetative, beneficial during reproductive and detrimental during ripening stage of the crop. Effects of increase in sunshine hours were detrimental during initial growth, active vegetative and reproductive stages, fluctuating during lag vegetative and beneficial during ripening stage of the crop.